Antibody responses to Schistosoma mansoni schistosomula antigens - Egesa, Moses (Parasite Immunol, 2018)
While antigens from Schistosoma schistosomula have been suggested as potential vaccine candidates, the association between antibody responses with schistosomula antigens and infection intensity at reinfection is not well known. Schistosoma mansoni‐infected individuals were recruited from a schistosomiasis endemic area in Uganda (n = 372), treated with 40 mg/kg praziquantel (PZQ) and followed up at five weeks and at one year post‐treatment. Pre‐treatment and five weeks post‐treatment immunoglobulin (Ig) E, IgG1 and IgG4 levels against recombinant schistosomula antigens rSmKK7, rSmLy6A, rSmLy6B and rSmTSP7 were measured using ELISA. Factors associated with detectable pre‐treatment or post‐treatment antibody response against the schistosomula antigens and the association between five‐week antibody responses and one year post‐treatment reinfection intensity among antibody responders were examined. Being male was associated with higher pre‐treatment IgG1 to rSmKK7, rSmLy6a and AWA. Five weeks post‐treatment antibody responses against schistosomula antigens were not associated with one year post‐treatment reinfection intensity among antibody responders’ antibody levels against rSmKK7, rSmLy6B and rSmTSP7 dropped, but increased against rSmLy6A, AWA and SEA at five weeks post‐treatment among antibody responders. S. mansoni‐infected individuals exhibit detectable antibody responses to schistosomula antigens that are affected by treatment. These findings indicate that schistosomula antigens induce highly varied antibody responses and could have implications for vaccine development.